Maternal mental disturbances and infantile development: perceptions on this reality - Barboza Cid, Maria Fernanda; Simões Matsukura, Thelma; Pessoa e Silva, Maria Denise (O Mundo da Saúde, 2012)
Considering observations in the literature that maternal mental disturbances constitute an important risk factor for the emotional development of children, the present study aims to identify the perception of mothers with mental disturbances and their children regarding this reality, focusing on aspects concerning maternal mental disturbances, care given to children and their self-perception. Subjects were four children from 7 to 12 years of age and their mothers. The used instruments were: scripts for semi-structured interviews applied to the mothers and the children and the Mini International Neuropsychiatric Interview (MINI), applied to the mothers. The main results indicate that children receive support from family members in daily life, play the role of carers and offer emotional support to their mothers at moments of crises caused by mental disturbances; they identify what they consider good and difficult in their lives and describe themselves in terms of aspects such as withdrawal and sadness.